Pengaruh Pertumbuhan Penjualan dan Profitabilitas terhadap Harga Saham melalui Struktur Modal - Amiruddin, Adeliana; Rahmisyari; Musafir (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2025)
The Effect of Sales Growth and Profitability on Share Price Through Capital Structure as an Intervening Variable in Pharmaceutical Companies Listed on the Indonesia Stock Exchange. Adeliana Amiruddin, ES22201021. Mr. Musafir SE, M.Si Supervisor I and Mrs. Dr. Rahmisyari, S.T., S.E., M.M. Supervisor IIThis study aims to analyze and explain the effect of sales growth and profitability on stock prices with capital structure as an intervening variable in the Pharmaceutical sub-sector listed on the Indonesia Stock Exchange. Pharmaceutical population consists of 11 companies using Purposive sampling so that 10 companies are sampled. The analysis method used is SEM PLS. The research results show that (i). Sales Growth (X1) has a significant effect on Share Price (Y) in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange in 2019-2023. (ii). Profitability (X2) has no significant effect on Share Price (Y) in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange in 2019-2023 (iii). Sales Growth (X1) has a significant effect on Capital Structure (Z) in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange in 2019-2023 (iv) Sales Growth (X1) has a significant effect on Capital Structure (Z) in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange in 2019-2023 (v). Capital Structure (Z) has a significant effect on Stock Price (Y) in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange in 2019-2023 (vii) Sales Growth (X1) has a significant effect on Stock Price (Y) through Capital Structure (Z) in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange in 2019-2023 (vii) Profitability (X2) has no significant effect on Stock Price (Y) through Capital Structure (Z) in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange in 2019-2023.